PENGARUH KETERAMPILAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP NEGERI 2 SATU ATAP BANDAR BEJAMBU KABUPATEN SERDANG BEDAGAI - Fira Novria Zulna (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
Teacher teaching skills are the skills or abilities of teachers in managing and implementing the learning process in schools that must be mastered for the realization of the goals of education. Learning motivation is a conscious effort to influence a person's behavior so that he is moved to act to do something so as to achieve the result or goal. certain. Based on the results of the pre-survey that the author did, it can be stated that there are still gaps in the learning process that occurs, this can be seen from some students' lack of motivation to learn. The formulation of the problem that the author proposes in this study is Is there an Influence of Teacher Skills on Learning Motivation for Islamic Religious Education Class VII at SMP Negeri 2 One Roof Bandar Bejambu. This research is a quantitative research and the nature of this research is correlation. The population of this study were all students of class VII at SMP Negeri 2 Satu Atap Bandar Bejambu totaling 51 students with a sample of 39 students because most of the students were non-Muslims. The method used is the questionnaire method as the main method and documentation as a supporting method. Meanwhile, for data analysis, the writer uses a hypothetical mean formula. Based on the results of the analysis carried out, it can be concluded that there is an influence between teacher teaching skills and student learning motivation. That is, teacher teaching skills (x) are included in the "very low" category. The magnitude of the influence with the variable of student learning motivation is 0.13 and the teacher's teaching skills and student motivation of SMP Negeri 2 One Roof are in the sufficient category. This shows that the teaching skills of teachers must always be considered and improved because they have an unfavorable impact on students' learning motivation.